Probing the Link Between Perception and Oscillations: Lessons from Transcranial Alternating Current Stimulation. (February 2020) - Cabral-Calderin, Yuranny; Wilke, Melanie
Brain oscillations are regarded as important for perception as they open and close time windows for neural spiking to enable the effective communication within and across brain regions. In the past, studies on perception primarily relied on the use of electrophysiological techniques for probing a correlative link between brain oscillations and perception. The emergence of noninvasive brain stimulation techniques such as transcranial alternating current stimulation (tACS) provides the possibility to study the causal contribution of specific oscillatory frequencies to perception. Here, we review the studies on visual, auditory, and somatosensory perception that employed tACS to probe the causality of brain oscillations for perception. The current literature is consistent with a causal role of alpha and gamma oscillations in parieto-occipital regions for visual perception and theta and gamma oscillations in auditory cortices for auditory perception. In addition, the sensory gating by alpha oscillations applies not only to the visual but also to the somatosensory domain. We conclude that albeit more refined perceptual paradigms and individualized stimulation practices remain to be systematically adopted, tACS is a promising tool for establishing a causal link between neural oscillations and perception.